PERFORMANCE OF EMPLOYEES IN THE PROCUREMENT DEPARTMENT OF PT. PETROKIMIA: WORK EFFECTIVENESS, JOB SATISFACTION - Djoko Soelistya; Agus Suharyanto; Eva Desembrianita; Mochamad Mochklas (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Expansion of PT. Petrokimia Gresik, which is getting bigger, requires large human resources as well. On the other hand, there is no permit for additional permanent manpower, while most of the human resources in the Procurement Compartment of PT. Peterokimia Gresik has entered its retirement period and there is no technology transfer for the migration of software used in the company, namely SAP software, so employee performance is ineffective. This study aims to analyze the effect of work effectiveness on employee satisfaction and performance, job satisfaction on employee performance. The research method used is quantitative research, with a population and sample of employees who are part of the Service Procurement Department and the Goods Procurement Department at PT. Petrokimia Gresik with a number of 50 respondents. All incoming and appropriate data will be analyzed by smartPLS. The results showed that work effectiveness has a significant positive effect on employee performance, job effectiveness has a significant positive effect on employee job satisfaction, job satisfaction has a positive but insignificant effect on employee performance and job satisfaction mediates the effect of work effectiveness on employee performance.